2021
DOI: 10.22491/2236-5907114069
|View full text |Cite
|
Sign up to set email alerts
|

Pandemia: janela de oportunidade para a privatização na educação básica do estado de São Paulo

Abstract: Este trabalho analisa como o modelo de ensino remoto, implementado em virtude da pandemia, agravou o processo de privatização da Rede Estadual de Ensino do Estado de São Paulo (REE-SP). Para analisar como o ensino remoto acentuou e conferiu novos contornos a esse fenômeno, utilizaram-se dados de contratos e termos de cooperação firmados pela Secretaria de Educação (SEDUC) em meio à pandemia e acessados via Serviço de Informação ao Consumidor (SIC) ou disponibilizados nos veículos oficiais do governo estadual. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…As far as instruction is concerned, based on lesson observations (n = 12), we recorded the most frequently implemented practices and found that, as illustrated in Table 7, the most frequent practices continue to be the methodologies of explanation and training [69], operationalized through the presentation of content in interaction with the students and/or using PowerPoint (version 2401) and interactive platforms; the resolution of exercises using worksheets and activity books; individual and pair work. Our observations did not provide us with the opportunity to observe more active and exploratory methodologies such as project work, research work, experimental activities or the flipped classroom technique.…”
Section: Focus On Student Learningmentioning
confidence: 99%
“…As far as instruction is concerned, based on lesson observations (n = 12), we recorded the most frequently implemented practices and found that, as illustrated in Table 7, the most frequent practices continue to be the methodologies of explanation and training [69], operationalized through the presentation of content in interaction with the students and/or using PowerPoint (version 2401) and interactive platforms; the resolution of exercises using worksheets and activity books; individual and pair work. Our observations did not provide us with the opportunity to observe more active and exploratory methodologies such as project work, research work, experimental activities or the flipped classroom technique.…”
Section: Focus On Student Learningmentioning
confidence: 99%
“…]". Second, practical and active learning at many schools is not merely instrumental, empty, and superficial; it is developed with an anthropological perspective, immersed in day-to-day cultural practices [50].…”
Section: 'Collaborative Preparation Of Students' Learning By Teachers...mentioning
confidence: 99%
“…The introduction of technology, so often confounded as school innovation itself [51], is increasingly an unavoidable tool in all innovation processes [28,50]. According to Figueiredo [50] (p. 253): "the idea of transforming education through technologies is absurd, but captivates our attention to the urgency of clarifying how to prepare the new generations for a world where technologies play a prominent role". 4.2.9.…”
Section: 'Collaborative Preparation Of Students' Learning By Teachers...mentioning
confidence: 99%
“…Emergency remote teaching and the indiscriminate use of technological resources over the course of the pandemic were adopted without due consideration of teachers' critical stances and of the accumulation of knowledge in the education field. The pandemic, on the one hand, was seen as a kind of "window of opportunity" by sectors linked to the education business, for the advancement of the so-called "modernization" process, expansion of technological tools in education, and greater openness for the intervention of private actors in public networks, in the provision of services, applications and digital platforms (Souza and Evangelista, 2020;Figueiredo Filho and Santos, 2021;Minto, 2021). On the other hand, the pressures for the face-to-face return elected teaching workers as the main target of criticism, which intensified the process of holding them accountable for the educational problems related to remote teaching.…”
Section: Introductionmentioning
confidence: 99%